2014
DOI: 10.1007/s10571-014-0027-z
|View full text |Cite
|
Sign up to set email alerts
|

d-Serine and Serine Racemase are Localized to Neurons in the Adult Mouse and Human Forebrain

Abstract: d-Serine, a co-agonist at the NMDA receptor (NMDAR), is synthesized from l-serine by the enzyme serine racemase (SR), which is heavily expressed in the forebrain. Although SR was originally reported to be localized exclusively to astrocytes, recent conditional knock out results demonstrate that little SR is expressed in forebrain astrocytes. As a consequence, the cellular location of its product, d-serine, in the brain is also uncertain. Immunocytochemistry now indicates that SR is expressed primarily in foreb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
110
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(117 citation statements)
references
References 32 publications
7
110
0
Order By: Relevance
“…A similar expression profile was observed for the synthesizing enzyme SRR, essential for conversion of l-serine to d-serine ( Figure 1, A and C). This expression profile supports previous studies showing that SRR and d-serine are primarily localized to neurons (12,(18)(19)(20).…”
Section: Phasic Release Of Neuronal D-serine Mediates Synaptic Transmsupporting
confidence: 91%
See 2 more Smart Citations
“…A similar expression profile was observed for the synthesizing enzyme SRR, essential for conversion of l-serine to d-serine ( Figure 1, A and C). This expression profile supports previous studies showing that SRR and d-serine are primarily localized to neurons (12,(18)(19)(20).…”
Section: Phasic Release Of Neuronal D-serine Mediates Synaptic Transmsupporting
confidence: 91%
“…NMDAR activation also requires the binding of a coagonist, such as d-serine or glycine. d-serine is considered a more likely binding partner for NMDAR in the hippocampus, since its expression patterns match NMDAR expression (12)(13)(14)(15)(16) and it has a higher affinity for the NMDAR glycine-binding site (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SRR was first identified as a glial enzyme (44), but more recent studies using SRR knockout mice have shown that SRR is expressed primarily in neurons found in the cerebral cortex and hippocampus (27,45). On the other hand, the possibility of SRR expression in astrocytes cannot be excluded, given the following evidence: (i) astrocyte-specific knockout of SRR reduces its expression level by 15% in the brain (28); (ii) eGFP designed to express under the SRR promoter in mice is detectable in hippocampal astrocytes (29); and (iii) enhancement of immunohistochemical signal makes astrocytic SRR observable (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This generated a new craze for NMDARs and laid the groundwork for a meaningful understanding of how these receptors impact cellular physiology and pathology. More recently, NMDARs have gained a new interest, as D-serine, a potential gliotransmitter released by astrocytes ( [16], but see [17]) was found to act as an endogenous co-agonist on their glycine-binding site [16,18 -21]. This discovery has made glia a possible regulator of NMDAR function and marked the emergence of an exciting cross-talk between the field of NMDARs and the expending & 2014 The Author(s) Published by the Royal Society.…”
Section: Introductionmentioning
confidence: 99%